THE REVIEW OF UTILIZATION EFFICIENCY YARDS SOME ECONOMIC ASPECTS OF THE REVISED - Irine Indrawati Syaifullah (UNEJ e-Proceeding, 2012)
The yard is a piece of land with certain the boundaries existing residential buildings on it that have the functional relations, both economic, biophysical and socio-cultural with its inhabitants. Utilization of their yards need attention are really considering the amount of donation provided by the yard for the welfare of farmers. These benefits include food selfsufficiency to maintain stability, increasing incomes and improving nutritional status, but there are still many who do not effectively utilize the yard. In connection with the development of garden land there are some things that should be asked is whether to use their yards to be successful in increasing revenue, labor productivity, improve cost efficiency and improve the allocation of results of operations of the yard. This research was conducted in villages Dawuhan, Situbondo district, county Situbondo. Data collection began on July 15, 1998 until August 28, 1998, by taking the primary data and secondary data. The study area is based on the consideration that the district Situbondo people already aware of the potential of land owned by the yard to increase revenue and as a source of nutrition, and the village is Dawuhan III championship race TOGA (Family Medicine Plant) in East Java in 1997.